2017
DOI: 10.1021/acs.chemmater.7b02759
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and Growth Mechanisms in Al2O3 deposited via Atomic Layer Deposition: Elucidating the Hydrogen Source

Abstract: In this work, we have quantitatively elucidated the source of the hydrogen content in the atomic layer deposition of Al2O3 at different temperatures (80–220 °C), by replacing the H2O precursor with heavy water (D2O) to use as a tracer and discern between the H coming from the unreacted metal precursor ligands and that from the unreacted −OD (hydroxyl) groups coming from the (heavy) water. The main source of impurities arises from the unreacted hydroxyl groups (−OD), reaching ∼18 atom % of deuterium at a deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 47 publications
(166 reference statements)
5
109
2
Order By: Relevance
“…as the amount of Ti precursor required to saturate the surface. Similarly to ALD, the first monolayer will not cover the surface with one continuous layer of TiO 2 due to the space left behind by the precursor ligands [51]. In contrast, precursor dosing according to OH density, as performed by Yan et al [30] resulted in undesired excess TiO 2 formation and poor deposition control.…”
Section: Deposition Of Tio 2 Overcoatsmentioning
confidence: 99%
“…as the amount of Ti precursor required to saturate the surface. Similarly to ALD, the first monolayer will not cover the surface with one continuous layer of TiO 2 due to the space left behind by the precursor ligands [51]. In contrast, precursor dosing according to OH density, as performed by Yan et al [30] resulted in undesired excess TiO 2 formation and poor deposition control.…”
Section: Deposition Of Tio 2 Overcoatsmentioning
confidence: 99%
“…As this number is not reasonable for the assumption that all the –OH groups are on the surface of the powder (i.e., it is theoretically and practically impossible to have 95 OH –groups on 1 nm 2 ), the calculated values suggest that most of the –OH groups are located inside the coating layer. This is caused by the incomplete consumption of –OH groups, which leads to hydrogen impurity in the film [66]. The existence of –OH strongly affects the density of Al 2 O 3 [61].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the experimental data obtained by Ylivaara et al have demonstrated that the low-temperature deposition of Al 2 O 3 using TMA and H 2 O is inherently associated with a considerable amount of impurities, especially hydrogen and carbon, which increase with decreasing deposition temperature [74]. The hydrogen impurity arises from the unreacted hydroxyl groups, which has recently been verified by Guerra-Nunez et al [66]. The degree of the GPC decrease at low temperatures is not well determined, and strongly depends on experimental conditions.…”
Section: Reaction Mechanism Of Al2o3 Ald Using Tma and H2o: A Briementioning
confidence: 97%
See 1 more Smart Citation
“…Al 2 O 3 is the most used TFE material that can protect against water and oxygen. [65] The 20 nm intermediate Al 2 O 3 layer reacts with water molecules and slowly produces a more compact Al 2 O 3 layer. Chang et al fabricated a 50 nm ALD Al 2 O 3 -coated PET layer as the encapsulation layer for PSCs, which significantly improved the environmental stability of the device.…”
Section: Thin Film Encapsulationmentioning
confidence: 99%